Pola Distribusi dan Intensitas Serangan Hama Utama Ostrinia furnacalis Guenee dan Helicoperva armigera Hubner pada Tanaman Jagung (Zea mays L.) di Kabupaten Merauke - Sembiring, Jefri (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This study aims to determine the distribution pattern and intensity of the attack of the corn cob and stem borer in Merauke Regency, Papua Province. This study uses purposive sampling method to determine the sampling by determining the specific characteristics that are in accordance with the research objectives, so that it is expected to determine the spread of insect pests. This research was conducted in 4 (four) villages in Semangga District and Tanah Miring District which have a lot of corn plants. One village was taken from each sub-district as the sampling location. Then each village is determined one location with an area of Â± 0.5 ha. Sampling at each location used the diagonal slice method, so that in each location there were five sub-locations. Each sub-location 20 clumps were taken, and observations were made every 10 days on 42-day-old plants until harvest. Based on the results of the study, the highest percentage of attacks by Ostrinia furnacalis was in Semangga District in Semangga Village (6.71%), and the lowest was in Waninggap Say Village (3.13%). Meanwhile, the highest percentage of Helicoperva armigera attacks was in Isanombias Village (7.12%), and the lowest was in Muram Sari Village (3.12%). The low pest population is caused by farmers already using insecticides in pest control. The distribution pattern of Ostrinia furnacalis and Helicoperva armigera in Merauke Regency was random, where individuals spread out in several places and grouped together in other places, this was due to the homogenous environment of maize cultivation.